169 An audit into the management of functional neurological disorder in Salford. Issue 9 (12th August 2022) - Houston, James; Cooper, Paul
Abstract : Background: Functional neurological disorder (FND) is a debilitating condition impacting all aspects of life. Poor understanding of FND, and lack of clinical service pathways, may result in poor management, compared to recent NICE (2021) Quality Standards. We audited patients diagnosed with FND after admission to Salford Royal, including the care pathways used. Methods: Salford Royal electronic patient records were accessed to populate an existing data collection tool used for analysis of neurological services. Patients admitted over a 4 month period were identified using ICD-10 coding (F44.5), with appropriate inclusion and exclusion criteria. We excluded patients with non-epileptic seizures as their prime diagnosis. Results: We identified 64 admitted patients, with 10 excluded. Of 54 patients analysed, 91% had a motor deficit, 53% had a sensory deficit, many therefore presenting with functional motor disorders, often with impaired mobility, and likely to benefit from a multidisciplinary team approach. 44% of patients had no documented management plan for their FND at discharge, and in 80% of patients follow-up plans were unclear. (It is acknowledged that limited access to outpatient letters from community services may have impacted results.) Conclusion: FND patients are being failed by our services, which are not meeting NICE Quality Standards. The unit is currently developing a multidisciplinary service for FND patients, which has proved challenging in the present climate. We plan to repeat the audit once our proposed service is established.